2010
DOI: 10.1084/jem.20100004
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors Foxo3a and Foxo1 couple the E3 ligase Cbl-b to the induction of Foxp3 expression in induced regulatory T cells

Abstract: The transcription factor Foxp3 is essential for optimal regulatory T (T reg) cell development and function. Here, we show that CD4+ T cells from Cbl-b RING finger mutant knockin or Cbl-b–deficient mice show impaired TGF-β–induced Foxp3 expression. These T cells display augmented Foxo3a phosphorylation, but normal TGF-β signaling. Expression of Foxo3a rescues Foxp3 expression in Cbl-b–deficient T cells, and Foxo3a deficiency results in defective TGF-β–driven Foxp3 induction. A Foxo3a-binding motif is present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
185
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(193 citation statements)
references
References 40 publications
6
185
1
1
Order By: Relevance
“…Foxo1-deficient mice show impaired development of Treg cells, and the cells that do develop are non-functional in vivo [95]. Finally, the FoxP3-promoter shows a series of Foxo-binding sites and mutagenesis studies have demonstrated a proximal Foxo-binding element that controls the FoxP3 promoter activity [96,97].…”
Section: Resultsmentioning
confidence: 99%
“…Foxo1-deficient mice show impaired development of Treg cells, and the cells that do develop are non-functional in vivo [95]. Finally, the FoxP3-promoter shows a series of Foxo-binding sites and mutagenesis studies have demonstrated a proximal Foxo-binding element that controls the FoxP3 promoter activity [96,97].…”
Section: Resultsmentioning
confidence: 99%
“…Female Foxo3 knockout mice were found to be sterile due to global primordial follicle activation with subsequent oocyte exhaustion (Castrillon et al ., 2003; Hosaka et al ., 2004). In addition, depletion of Foxo3 resulted in deficient development of regulatory T cells with consequent organ inflammation by a mechanism also involving Foxo1 (Harada et al ., 2010; Kerdiles et al ., 2010). Foxo4 and Foxo6 knockout mice present with only mild phenotypes (Zhu et al ., 2011; Salih et al ., 2012).…”
Section: Animal Modelsmentioning
confidence: 99%
“…Foxo1 controls Foxp3 promoter activity, regulating the differentiation of natural Tregs [23,24]. FOXO1 and FOXO3, which are FOXP3-inducing transcription factors, are also upregulated in ILT3-Fc-treated CD8 T cells, although the amplitude of induction was slightly less than twofold.…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%